Job placement via private vs. public employment agencies: Investigating selection effects and job match quality in Germany - Adam Ayaita; Christian Grund; Lisa Pütz (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Employment agencies aim to match individuals to appropriate jobs. There are public and private employment agencies, which co-exist in many countries. Selection effects may be relevant in the sense that private agencies potentially engage in 'cream-skimming' by prioritizing highly qualified workers. The resulting job match quality is also important from an individual, a firm, and a society perspective. We examine the selection into job placement via private and public employment agencies as well as the resulting job match qualities, taking a job-market reform in Germany into account: the introduction of vouchers for private job placements. Using representative German panel data, we find that cream-skimming is significantly less pronounced under the voucher policy, as private agencies shift the focus toward unemployed individuals with a voucher. In addition, we find evidence based on propensity score matching estimations that private agencies tend to create better matches than their public counterparts.
Keywords: J64; L33; M5; 330; Cream-skimming; employment agencies; job match quality; job placement; job search; selection; vouchers